Fluid-structure interactions study on hydraulic structures: A review - Zawawi M.H.; Hassan N.H.; Ramli M.Z.; Zahari N.M.; Radzi M.R.M.; Saleha A.; Salwa A.; Sidek L.M.; Muda Z.C.; Kamaruddin M.A. (American Institute of Physics Inc., 2023)
Fluid-structure interactions (FSI) occurs when fluid flow causes deformation of the structure and in turn, the deformation changes the boundary conditions of the fluid flow. FSI is considered essential in the design of many engineering systems. The example of application FSI to engineering system is hydraulic structures. Hydraulic structures are purposely created and built to perform controlled, conveyed and contained water. It will be more useful to consumers if it is functioning satisfactorily. In order to study the effect of the FSI on hydraulic structure, computational fluid dynamic (CFD) is used to analyse the data. The main objective of this paper is to review the studies conducted on FSI within hydraulic structures. The study of FSI on hydraulic structure is devoted to the solution of the equation of fluid flow through the use of computer. 2018 Author(s).